Ultrahigh-rate interface modified silicon-carbon negative electrode material

By using a composite structure of porous carbon, inner interface modification layer, silicon and coated carbon layer in the silicon carbon negative electrode material, the shortcomings of silicon carbon negative electrode material in high rate performance and cycle stability are solved, and efficient and stable lithium ion storage is achieved.

CN119890269APending Publication Date: 2025-04-25XUANCHENG SILIKO NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510102626.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

While providing high capacity, silicon carbon anode materials face problems such as volume expansion, poor cycle stability and high electrochemical impedance, and cannot meet the needs of high rate performance.

Method used

The composite structure of porous carbon, inner interface modification layer, silicon and coated carbon layer is adopted to deposit the inner interface modification layer by gas or liquid phase modification method to form a stable interface, inhibit the expansion of silicon volume and improve the ion transport capability.

Benefits of technology

It significantly improves the rate performance and cycle stability of the negative electrode material, reduces volume expansion, enhances mechanical strength, and simplifies the production process, with the advantages of low cost and high productivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005254568300000081
    Figure BDA0005254568300000081
Patent Text Reader

Abstract

The invention relates to the technical field of negative electrode material modification, and relates to an ultrahigh-rate interface modified silicon-carbon negative electrode material which comprises the following components in parts by weight: 1-5 parts of porous carbon, 0.01-0.05 part of an internal interface modification layer, 1-5 parts of carbon dioxide and 1-5 parts of acetylene, the silicon-carbon negative electrode material is of a composite structure of porous carbon, an inner interface modification layer, silicon, the inner interface modification layer and a coating carbon layer, the inner interface modification layer is one or a combination of more of metal oxide, amorphous silicon oxide and crystalline silicon oxide, and the inner interface modification layer is deposited on the porous carbon through a gas phase or liquid phase modification method. A precursor is one or a combination of more of monosilane, disilane, chlorosilane, dichlorosilane, trichlorosilane, silicon tetrachloride, tetrabutyl titanate, aluminum hydroxide, aluminum chloride, magnesium powder, aluminum powder or titanium powder, and a porous carbon / oxide / silicon / oxide / coated carbon layer composite structure is adopted, so that volume expansion is effectively inhibited, the cycle performance of the material is improved, and the rate capability of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode material modification, and in particular to an ultra-high rate interface modified silicon-carbon negative electrode material. Background Art

[0002] As an advanced energy storage device, lithium batteries have been widely used in portable electronic products, electric vehicles and large-scale energy storage systems. They have the advantages of high energy density, low self-discharge rate and long cycle life. They are the leaders in current energy storage technology. With the increasingly severe energy crisis and environmental pollution problems, the development of efficient and environmentally friendly lithium battery technology is particularly important. The performance of negative electrode materials, as a key component of lithium batteries, directly affects the overall performance of the battery. Negative electrode materials need to have good electronic conductivity, ion diffusion and structural stability. At present, commercial lithium batteries mainly use graphite negative electrode materials, but their specific capacity is close to the theoretical limit and it is difficult to meet the needs of future energy storage technology. Therefore, the development of high specific capacity negative electrode materials has become a research hotspot.

[0003] Silicon has attracted more and more attention from the scientific research and industrial circles due to its high lithium storage capacity and abundant reserves. However, the current silicon-carbon negative electrode materials, while providing high capacity, face the challenges of huge volume expansion (>300%) and cycle stability. In addition, they cannot solve the formation of a large number of Si-C bonds inside silicon-carbon, cannot form a stable SEI, and produce serious electrochemical impedance, which cannot meet the rate performance requirements of power batteries. In view of this, an ultra-high rate interface-modified silicon-carbon negative electrode material is provided. Summary of the invention

[0004] The purpose of the present invention is to provide an ultra-high rate interface modified silicon-carbon negative electrode material to solve the problems of instability, low rate performance and low cycle retention rate of the silicon-carbon negative electrode material mentioned in the above background technology.

[0005] To achieve the above-mentioned purpose, the present invention aims to provide an ultra-high rate interface-modified silicon-carbon negative electrode material, comprising the following components in parts by weight: 1-5 parts by weight of porous carbon, 0.01-0.05 parts by weight of an internal interface modification layer, 1-5 parts by weight of carbon dioxide, and 1-5 parts by weight of acetylene, wherein the silicon-carbon negative electrode material is a composite structure of porous carbon, an internal interface modification layer, silicon, an internal interface modification layer and a coated carbon layer, the internal interface modification layer is one or more combinations of metal oxides, amorphous silicon oxide and crystalline silicon oxide, the internal interface modification layer is deposited on the porous carbon by a gas phase or liquid phase modification method, and the precursor is one or more combinations of monosilane, disilane, chlorosilane, dichlorosilane, trichlorosilane, silicon tetrachloride, tetrabutyl titanate, aluminum hydroxide, aluminum chloride, magnesium powder, aluminum powder or titanium powder.

[0006] As a further improvement of the technical solution, the microporosity of the porous carbon is 80-99%.

[0007] As a further improvement of the technical solution, the mass of the inner interface modification layer accounts for 5-10wt% of the total mass of the silicon-carbon negative electrode material.

[0008] As a further improvement of the technical solution, the pore volume of the porous carbon@oxide material is 0.7-1.2, and the microporosity is 50-100%.

[0009] As a further improvement of the technical solution, the silicon in the interface layer accounts for 5-10wt% of the total mass of the silicon-carbon negative electrode material.

[0010] As a further improvement of the technical solution, when the inner interface modification layer is silicon oxide, the silicon oxide is amorphous silicon oxide or crystalline silicon oxide, and the specific preparation method of the interface modified silicon-carbon negative electrode material is as follows:

[0011] S1.1. Place porous carbon in a fluidized bed, evacuate with nitrogen flow rate of 1-5 L / min until the oxygen content of tail gas is less than 100 ppm, reduce nitrogen flow rate to 1-3 L / min, raise temperature to 400-500 °C at 5 °C / min, keep warm for 30-40 min, introduce 1-3 L / min gas precursor into the fluidized bed cavity, use nitrogen as carrier gas, set the whole flow rate to 10-15 L / min, and introduce time for 10-30 min;

[0012] S1.2, turn off the gas precursor, introduce 0.5-2.5L / min carbon dioxide, react for 2-3h, turn off the carbon dioxide, and flush the fluidized bed cavity with 1-5L / min nitrogen for 2-3h;

[0013] S1.3, raising the temperature of the equipment to 800-900°C to heat-treat the obtained porous carbon@a-SiO to obtain porous carbon@c-SiO, during which the nitrogen flow rate is 1-3L / min and the temperature is kept for 1-2h;

[0014] S1.4, cool down to 400-500℃, continue to introduce 1-3L / min of gas precursor, after vapor deposition for 6-8h, turn off the gas precursor to obtain porous carbon@c-SiO@a-Si;

[0015] S1.5, introduce 1-3L / min nitrogen and raise the temperature to 700-800°C, keep the temperature for 2-3h, and obtain porous carbon@c-SiO@c-Si;

[0016] S1.6, cool down to 400-500℃, continue to introduce 1-3L / min of gas precursor, and after vapor deposition for 6-8h, turn off the gas precursor to obtain porous carbon@c-SiO@c-Si@a-SiO;

[0017] S1.7. Heat the equipment to 600-800°C, turn on acetylene, the acetylene flow rate is 1-5L / min, and perform vapor deposition for 1-2h to obtain silicon-carbon negative electrode material.

[0018] As a further improvement of the technical solution, the gas concentration of the gas precursor is 5%-95%

[0019] As a further improvement of the technical solution, when the inner interface modification layer is a metal oxide, the specific preparation method of the interface modified silicon-carbon negative electrode material is as follows:

[0020] S2.1, placing porous carbon in a vacuum coating chamber, selecting a metal as a precursor, vaporizing it using a high-temperature vaporization device, and vapor-depositing the porous carbon at 700-800°C to obtain a porous carbon@metal material;

[0021] S2.2, put the obtained sample into a fluidized bed, raise the temperature to 500-600°C, introduce 0.5-2.5L / min carbon dioxide, react for 2-3h, turn off the carbon dioxide, and flush the fluidized bed cavity with 1-5L / min nitrogen for 2-3h;

[0022] S2.3, cool down to 400-450°C, continue to introduce 1-2L / min of gas precursor, and after vapor deposition for 4-5h, turn off the gas precursor to obtain porous carbon@metal oxide@a-Si;

[0023] S2.4, introduce 1-3L / min nitrogen and raise the temperature to 700-800°C, keep the temperature for 2-3h, and obtain porous carbon@metal oxide@c-Si;

[0024] S2.5, cool down to 400-500°C at 5°C / min, keep warm for 30-40min, introduce 1-3L / min gas precursor into the fluidized bed cavity, use nitrogen as carrier gas, set the whole flow rate to 10-15L / min, introduce time for 10-30min, turn off the gas precursor, introduce 0.5-2.5L / min carbon dioxide, react for 2-3h, turn off carbon dioxide, flush the fluidized bed cavity with 1-5L / min nitrogen for 2-3h, and obtain porous carbon@metal oxide@c-Si@a-SiO;

[0025] S2.6. Heat the equipment to 600-800°C, turn on acetylene, the acetylene flow rate is 1-5L / min, and perform vapor deposition for 1-2h to obtain silicon-carbon negative electrode material.

[0026] As a further improvement of the technical solution, the mass of the metal material accounts for 3-4% of the total mass of the silicon-carbon negative electrode material.

[0027] As a further improvement of the technical solution, the purity of the metal powder is 99.5-99.8%.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] In this ultra-high rate interface-modified silicon-carbon negative electrode material, a porous carbon / oxide / silicon / oxide / coated carbon layer composite structure is adopted. The oxide layer has higher stability than silicon, and can effectively inhibit the volume expansion of silicon when lithium is inserted, thereby improving the cycle performance of the material. At the same time, the lithium salt formed by the oxide provides higher ion transmission, further improving the rate performance of the material. In addition, the silicon in the interface layer provides a high lithium ion channel, and the oxides on both sides isolate the silicon and porous carbon, inhibiting the formation of silicon-carbon bonds during high-temperature carbon coating, thereby increasing the carbon coating temperature and improving the rate performance of the material. In addition, the use of heat treatment to convert a-Si into c-Si can improve the mechanical strength of the material, further inhibiting the volume expansion while improving the rate, and the synthesis process designed by the method is completed in a fluidized bed reactor, realizing one-stop synthesis, greatly reducing the complexity of material production, and has the advantages of low cost and high production capacity. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0031] An ultra-high rate interface-modified silicon-carbon negative electrode material, comprising the following components in parts by weight: 1-5 parts by weight of porous carbon, 0.01-0.05 parts by weight of an internal interface modification layer, 1-5 parts by weight of carbon dioxide, and 1-5 parts by weight of acetylene, wherein the silicon-carbon negative electrode material is a composite structure of porous carbon, an internal interface modification layer, silicon, an internal interface modification layer, and a coated carbon layer, the internal interface modification layer is one or more combinations of metal oxides, amorphous silicon oxide, and crystalline silicon oxide, the internal interface modification layer is deposited on the porous carbon by a gas phase or liquid phase modification method, and the precursor is one or more combinations of monosilane, disilane, chlorosilane, dichlorosilane, trichlorosilane, silicon tetrachloride, tetrabutyl titanate, aluminum hydroxide, aluminum chloride, magnesium powder, aluminum powder, or titanium powder;

[0032] The metal oxide of the inner interface modification layer is preferably aluminum oxide among aluminum oxide, magnesium oxide and titanium oxide;

[0033] Preferably, monosilane is used as a precursor for preparing amorphous silicon oxide and crystalline silicon oxide, and aluminum powder is used as a precursor for preparing metal oxide.

[0034] Example 1: In this example, the specific preparation method of the ultra-high rate interface modified silicon-carbon negative electrode material is as follows:

[0035] S3.1. Place 1 part by weight of porous carbon with a microporosity of 90% into a fluidized bed, discharge the fluidized bed at a nitrogen flow rate of 5 L / min until the oxygen content of the tail gas is less than 100 ppm, reduce the nitrogen flow rate to 1 L / min, raise the temperature to 450°C at 5°C / min, keep warm for 30 min, introduce 2 L / min of monosilane into the fluidized bed cavity, use nitrogen as the carrier gas, set the flow rate to 10 L / min throughout the process, and introduce it for 30 min;

[0036] S3.2, turn off the monosilane, introduce 1L / min carbon dioxide, react for 2h, turn off the carbon dioxide, and flush the fluidized bed cavity with 5L / min nitrogen for 2h;

[0037] S3.3, raising the temperature of the equipment to 900°C to heat-treat the obtained porous carbon@a-SiO to obtain porous carbon@c-SiO, during which the nitrogen flow rate is 1 L / min and the temperature is kept for 2 hours;

[0038] S3.4, cooling down to 450°C, continuing to introduce monosilane at 2 L / min, after vapor deposition for 6 h, turning off the monosilane to obtain porous carbon@c-SiO@a-Si;

[0039] S3.5, introduce 1L / min nitrogen and raise the temperature to 700°C, keep the temperature for 2h, and obtain porous carbon@c-SiO@c-Si;

[0040] S3.6, cooling to 450°C, continuing to introduce 2 L / min of monosilane, after vapor deposition for 6 h, turning off the monosilane to obtain porous carbon @c-SiO@c-Si@a-SiO;

[0041] S3.7. Heat the equipment to 600°C, turn on acetylene, the acetylene flow rate is 1L / min, and perform vapor deposition for 2h to obtain silicon-carbon negative electrode material.

[0042] Example 2: In this example, the specific preparation method of the ultra-high rate interface modified silicon-carbon negative electrode material is as follows:

[0043] S2.1, put 1 kg of porous carbon with a microporosity of 90% into a vacuum coating chamber, select metal aluminum powder as a precursor, use a high-temperature vaporization device to vaporize, and evaporate the porous carbon at 700°C to obtain a porous carbon@aluminum material;

[0044] S2.2, put the obtained sample into a fluidized bed, raise the temperature to 600°C, introduce 1L / min carbon dioxide, react for 2h, turn off the carbon dioxide, and flush the fluidized bed cavity with 5L / min nitrogen for 2h;

[0045] S2.3, cooling to 450°C, continuing to introduce 2L / min of monosilane, after vapor deposition for 5h, turning off the monosilane to obtain porous carbon@alumina@a-Si;

[0046] S2.4, introduce 1L / min nitrogen gas and raise the temperature to 700℃, keep the temperature for 2h, and obtain porous carbon@alumina@c-Si;

[0047] S2.5, cool down to 450℃ at 5℃ / min, keep warm for 30min, introduce 2L / min monosilane into the fluidized bed cavity, use nitrogen as carrier gas, set the flow rate to 10L / min, introduce for 30min, turn off monosilane, introduce 1L / min carbon dioxide, react for 2h, turn off carbon dioxide, flush the fluidized bed cavity with 5L / min nitrogen for 2h, and obtain porous carbon@alumina@c-Si@a-SiO;

[0048] S2.6. Heat the equipment to 600°C, turn on acetylene, the acetylene flow rate is 1L / min, and perform vapor deposition for 2h to obtain silicon-carbon negative electrode material.

[0049] Example 3: In this example, the specific preparation method of the ultra-high rate interface modified silicon-carbon negative electrode material is as follows:

[0050] S3.1. Place 1 part by weight of porous carbon with a microporosity of 90% into a fluidized bed, discharge the fluidized bed at a nitrogen flow rate of 5 L / min until the oxygen content of the tail gas is less than 100 ppm, reduce the nitrogen flow rate to 1 L / min, raise the temperature to 450°C at 5°C / min, keep warm for 30 min, introduce 2 L / min of monosilane into the fluidized bed cavity, use nitrogen as the carrier gas, set the flow rate to 10 L / min throughout the process, and introduce it for 30 min;

[0051] S3.2, turn off the monosilane, introduce 1L / min carbon dioxide, react for 2h, turn off the carbon dioxide, and flush the fluidized bed cavity with 5L / min nitrogen for 2h;

[0052] S3.3, raising the temperature of the equipment to 900°C to heat-treat the obtained porous carbon@a-SiO to obtain porous carbon@c-SiO, during which the nitrogen flow rate is 1 L / min and the temperature is kept for 2 hours;

[0053] S3.4, cooling to 450°C, continuing to introduce 2L / min of monosilane, after vapor deposition for 6 hours, turning off the monosilane to obtain porous carbon@c-SiO@a-Si;

[0054] S3.5, continue to introduce monosilane at 2 L / min, and after vapor deposition for 6 hours, turn off the monosilane to obtain porous carbon @c-SiO@a-Si@a-SiO;

[0055] S3.7. Heat the equipment to 600°C, turn on acetylene, the acetylene flow rate is 1L / min, and perform vapor deposition for 2h to obtain silicon-carbon negative electrode material.

[0056] Comparative Example 1: The method of Example 1 was adopted to prepare porous carbon @a-Si as a silicon-carbon negative electrode material.

[0057] Comparative Example 2: The method of Example 1 was adopted to prepare a porous carbon / oxide / silicon / coated carbon layer composite structure.

[0058] The present invention prepares an ultra-high rate interface modified silicon-carbon negative electrode material, which has good high stability, high rate and high cycle retention rate in the application of the negative electrode material modification technology field. The specific detection is shown in the following table;

[0059] First, the silicon-carbon negative electrode material is slurried with a conductive agent and a binder and coated on a copper foil current collector to obtain a negative electrode sheet. The electrode and other components are assembled into a button battery, using lithium metal as the positive electrode, a silicon-carbon composite material as the negative electrode, and LiPF6 / EC+DMC electrolyte to form a 2032 button battery.

[0060] 1.5V capacity refers to the maximum discharge capacity per unit mass of material measured at a cut-off voltage of 1.5V, which reflects the energy storage capacity of the material at a specific voltage, that is, the theoretical capacity or actual available capacity of the material. A battery tester is used to perform constant current charge and discharge tests at a cut-off voltage of 1.5V, and the maximum capacity at the first discharge is recorded.

[0061] The 1.5V first efficiency refers to the ratio of the first discharge capacity to the first charge capacity, which reflects the reversibility of the material during the first cycle, that is, the coulombic efficiency of the material during the first charge and discharge. The first charge and discharge cycle is carried out at a cut-off voltage of 1.5V, and the first discharge capacity and the first charge capacity are recorded. The first efficiency = (charge capacity / discharge capacity) × 100%, which is obtained by calculating the ratio of the two.

[0062] The capacity retention rate after 100 cycles of 1C / 2C / 3C refers to the percentage of remaining capacity relative to the initial discharge capacity after 100 cycles at a current density of 1C / 2C / 3C. It reflects the cycle stability of the material at a standard rate, that is, the long-term performance of the material at a normal charge and discharge rate. At a current density of 1C / 2C / 3C, 100 cycles of charge and discharge tests were performed at a cut-off voltage of 1.5V, and the discharge capacity after each cycle was recorded. Capacity retention rate = (initial capacity / capacity after n cycles) × 100%, where n is the number of cycles. The capacity retention rate after 100 cycles at different rates is calculated.

[0063] The battery expansion rate after 100 cycles refers to the ratio of the volume expansion of the battery to the original volume after 100 cycles. It reflects the volume change of the material during the cycle and is an important indicator for evaluating the structural stability and safety of the material. The battery size change before and after the cycle is measured, and the initial thickness of the battery is measured with a micrometer. The battery thickness is measured again after 100 cycles, and the volume expansion rate is calculated by (thickness after cycle - initial thickness) / initial thickness × 100%.

[0064] The obtained data are shown in Table 1

[0065] Table 1 Performance data of an ultra-high rate interface modified silicon-carbon negative electrode material of Examples 1-3 and Comparative Examples 1-2

[0066]

[0067] By comparing Example 1-3 with Comparative Example 1-2, it can be seen that in an ultra-high rate interface-modified silicon-carbon negative electrode material, the porous carbon / oxide / silicon / oxide / coated carbon layer composite structure will have a significant impact on the performance of the negative electrode material.

[0068] According to Example 1 and Example 2, the inner interface modification layer is silicon oxide or aluminum oxide, and the performance of an ultra-high rate interface-modified silicon-carbon negative electrode material is not greatly affected. This is because silicon oxide and aluminum oxide are both metal oxides with good chemical stability, which can alleviate the volume change of silicon during the charge and discharge process, provide a relatively stable interface, reduce the side reactions between silicon and the electrolyte, and provide an ion transfer path, so the performance of the negative electrode material is better.

[0069] According to Example 1 and Example 3, whether the silicon in the interface layer is crystalline silicon or amorphous silicon has a certain influence on the silicon-carbon negative electrode material. This is because crystalline silicon has a clear lattice structure, and amorphous silicon does not have a long-range ordered lattice structure, but presents a short-range ordered amorphous structure. Therefore, crystalline silicon has higher mechanical strength, which helps to improve the overall structural stability of the material, inhibit the expansion of the material, and reduce the risk of structural damage during the charge and discharge process, thereby improving the cycle stability. In addition, the structure of crystalline silicon is more ordered, which helps the rapid transmission of lithium ions, thereby improving the rate performance, and therefore the performance of crystalline silicon is better than that of amorphous silicon.

[0070] According to the above test experiments, Example 1 is used as the optimal example and compared with Comparative Examples 1-2 respectively.

[0071] By comparing Example 1 with Comparative Example 1, it can be seen that the porous carbon @a-Si is prepared as a silicon-carbon negative electrode material, and the sandwich structure formed by oxide composite silicon is not used. The performance of the negative electrode material is significantly reduced. This is because the negative electrode material with a sandwich structure can better alleviate the stress caused by the volume change of silicon during the charging and discharging process, and inhibit the volume expansion of silicon when lithium is inserted, thereby improving the mechanical stability of the material and improving the cycle performance of the material. In addition, the oxides on both sides can isolate silicon and porous carbon, inhibit the formation of silicon-carbon bonds during high-temperature carbon coating, thereby increasing the carbon coating temperature and improving the rate performance of the material. The porous carbon @a-Si has no composite oxide and lacks an inhibitory effect, which easily leads to volume expansion and poor cycle stability.

[0072] By comparing Example 1 and Comparative Example 2, it can be seen that the porous carbon / oxide / silicon / coated carbon layer composite structure has a certain effect on the silicon-carbon negative electrode material compared to the porous carbon / oxide / silicon / oxide / coated carbon layer composite structure. This is because the double-layer oxide structure can provide better mechanical stability, alleviate the stress caused by the volume change of silicon, and help protect the silicon layer from structural damage. Therefore, it has better cycle stability than the single-layer oxide structure.

[0073] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only preferred examples of the present invention, and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. An ultra-high rate interface-modified silicon-carbon negative electrode material, characterized in that: The invention comprises the following components in parts by weight: 1-5 parts by weight of porous carbon, 0.01-0.05 parts by weight of inner interface modification layer, 1-5 parts by weight of carbon dioxide, and 1-5 parts by weight of acetylene; Among them, the silicon-carbon negative electrode material is a composite structure of porous carbon, an inner interface modification layer, silicon, an inner interface modification layer and a coating carbon layer; The inner interface modification layer is one or more combinations of metal oxide, amorphous silicon oxide and crystalline silicon oxide; The inner interface modification layer is deposited on the porous carbon by a gas phase or liquid phase modification method; The precursor is one or more combinations of monosilane, disilane, chlorosilane, dichlorosilane, trichlorosilane, silicon tetrachloride, tetrabutyl titanate, aluminum hydroxide, aluminum chloride, magnesium powder, aluminum powder or titanium powder.

2. The ultra-high rate interface-modified silicon-carbon negative electrode material according to claim 1, characterized in that: The microporosity of the porous carbon is 80-99%.

3. The ultra-high rate interface modified silicon-carbon negative electrode material according to claim 1, characterized in that: The mass of the inner interface modification layer accounts for 5-10wt% of the total mass of the silicon-carbon negative electrode material.

4. The ultra-high rate interface modified silicon-carbon negative electrode material according to claim 1, characterized in that: The porous carbon@oxide material has a pore volume of 0.7-1.2 and a microporosity of 50-100%.

5. The ultra-high rate interface modified silicon-carbon negative electrode material according to claim 1, characterized in that: The silicon in the interface layer accounts for 5-10 wt% of the total mass of the silicon-carbon negative electrode material.

6. The ultra-high rate interface modified silicon-carbon negative electrode material according to claim 1, characterized in that: When the inner interface modification layer is silicon oxide, the silicon oxide is amorphous silicon oxide or crystalline silicon oxide, and the specific preparation method of the interface modified silicon-carbon negative electrode material is as follows: S1.

1. Place porous carbon in a fluidized bed, evacuate with nitrogen flow rate of 1-5 L / min until the oxygen content of tail gas is less than 100 ppm, reduce nitrogen flow rate to 1-3 L / min, raise temperature to 400-500 °C at 5 °C / min, keep warm for 30-40 min, introduce 1-3 L / min gas precursor into the fluidized bed cavity, use nitrogen as carrier gas, set the whole flow rate to 10-15 L / min, and introduce time for 10-30 min; S1.2, turn off the gas precursor, introduce 0.5-2.5L / min carbon dioxide, react for 2-3h, turn off the carbon dioxide, and flush the fluidized bed cavity with 1-5L / min nitrogen for 2-3h; S1.3, raising the temperature of the equipment to 800-900°C to heat-treat the obtained porous carbon@a-SiO to obtain porous carbon@c-SiO, during which the nitrogen flow rate is 1-3L / min and the temperature is kept for 1-2h; S1.4, cool down to 400-500°C, continue to introduce 1-3L / min of gas precursor, and after vapor deposition for 6-8h, turn off the gas precursor to obtain porous carbon@c-SiO@a-Si; S1.5, introduce 1-3L / min nitrogen and raise the temperature to 700-800°C, keep the temperature for 2-3h, and obtain porous carbon@c-SiO@c-Si; S1.6, cool down to 400-500℃, continue to introduce 1-3L / min of gas precursor, and after vapor deposition for 6-8h, turn off the gas precursor to obtain porous carbon@c-SiO@c-Si@a-SiO; S1.

7. Heat the equipment to 600-800°C, turn on acetylene, the acetylene flow rate is 1-5L / min, and perform vapor deposition for 1-2h to obtain silicon-carbon negative electrode material.

7. The ultra-high rate interface-modified silicon-carbon negative electrode material according to claim 6, characterized in that: The gas concentration of the gas precursor is 5%-95%.

8. The ultra-high rate interface modified silicon-carbon negative electrode material according to claim 1, characterized in that: When the inner interface modification layer is a metal oxide, the specific preparation method of the interface modified silicon-carbon negative electrode material is as follows: S2.1, placing porous carbon in a vacuum coating chamber, selecting a metal as a precursor, vaporizing it using a high-temperature vaporization device, and vapor-depositing the porous carbon at 700-800°C to obtain a porous carbon@metal material; S2.2, put the obtained sample into a fluidized bed, raise the temperature to 500-600°C, introduce 0.5-2.5L / min carbon dioxide, react for 2-3h, turn off the carbon dioxide, and flush the fluidized bed cavity with 1-5L / min nitrogen for 2-3h; S2.3, cool down to 400-450°C, continue to introduce 1-2L / min of gas precursor, and after vapor deposition for 4-5h, turn off the gas precursor to obtain porous carbon@metal oxide@a-Si; S2.4, introduce 1-3L / min nitrogen and raise the temperature to 700-800°C, keep the temperature for 2-3h, and obtain porous carbon@metal oxide@c-Si; S2.5, cool down to 400-500°C at 5°C / min, keep warm for 30-40min, introduce 1-3L / min gas precursor into the fluidized bed cavity, use nitrogen as carrier gas, set the whole flow rate to 10-15L / min, introduce time for 10-30min, turn off the gas precursor, introduce 0.5-2.5L / min carbon dioxide, react for 2-3h, turn off carbon dioxide, flush the fluidized bed cavity with 1-5L / min nitrogen for 2-3h, and obtain porous carbon@metal oxide@c-Si@a-SiO; S2.

6. Heat the equipment to 600-800°C, turn on acetylene, the acetylene flow rate is 1-5L / min, and perform vapor deposition for 1-2h to obtain silicon-carbon negative electrode material.

9. The ultra-high rate interface-modified silicon-carbon negative electrode material according to claim 8, characterized in that: The mass of the metal material accounts for 3-4% of the total mass of the silicon-carbon negative electrode material.

10. The ultra-high rate interface modified silicon-carbon negative electrode material according to claim 8, characterized in that: The purity of the metal powder is 99.5-99.8%.